2006
DOI: 10.1152/jn.00854.2005
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Regulates Current Density and Frequency-Dependent Inhibition of Sodium Channel Nav1.8 in DRG Neurons

Abstract: -Hajj. Calmodulin regulates current density and frequency-dependent inhibition of sodium channel Na v 1.8 in DRG neurons. J Neurophysiol 96: 97-108, 2006. First published April 5, 2006 doi:10.1152/jn.00854.2005. Sodium channel Na v 1.8 produces a slowly inactivating, tetrodotoxin-resistant current, characterized by recovery from inactivation with fast and slow components, and contributes a substantial fraction of the current underlying the depolarizing phase of the action potential of dorsal root ganglion (DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…Slow inactivation has been reported in various mammalian neuronal cells including rat hippocampal neurons (48), tetrodotoxin-resistant DRG neurons (23), and cultured neuroblastoma cells (49) and is important to firing adaptation. Several molecular partners and membrane proteins have been reported to modulate Na ϩ channel slow inactivation, including ␤ 1-4 subunits, ankyrin G (50), and calmodulin (25). Our data suggest selective AQP1 modulation of Na v 1.8 but not Na v 1.7.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Slow inactivation has been reported in various mammalian neuronal cells including rat hippocampal neurons (48), tetrodotoxin-resistant DRG neurons (23), and cultured neuroblastoma cells (49) and is important to firing adaptation. Several molecular partners and membrane proteins have been reported to modulate Na ϩ channel slow inactivation, including ␤ 1-4 subunits, ankyrin G (50), and calmodulin (25). Our data suggest selective AQP1 modulation of Na v 1.8 but not Na v 1.7.…”
Section: Discussionmentioning
confidence: 58%
“…Na ϩ channels Na v 1.1 to Na v 1.9 are composed of a large ␣ subunit containing the pore-and voltage-sensing machinery and several auxiliary ␤ subunits (50). Only a few other proteins have been reported to interact directly with Na v 1.8, including annexin II light chain (51), calmodulin (25), and clathrin-associated protein-1A (42). The immunoprecipitation and single molecule tracking indicated a physical interaction between AQP1 and Na v 1.8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1C), is an important residue of the calmodulin binding IQ motif (Bahler and Rhoads, 2002), which is implicated in the modulation of several Na + channel isoforms (Young and Caldwell, 2005;Choi et al, 2006;Biswas et al, 2008), and we have shown that calmodulin can rescue hNa v 1.1-M1841T (Rusconi et al, 2007). Although R1916G should inhibit calmodulin binding, we tested the effect of cotransfection of calmodulin and found, indeed, that there was no significant modification of hNa v 1.1-R1916G current density ( Fig.…”
Section: Effects Of Other Interacting Proteinsmentioning
confidence: 90%
“…In fact, it has been shown that calmodulin can differentially modulate several Na + channel isoforms, inducing functional effects that depend on the isoform and on the cell type used for the experiments (Young and Caldwell, 2005;Choi et al, 2006;Biswas et al, 2008). However, both reduction of cell surface expression and negative shift of the inactivation curve, which are two of the effects caused by R1916G, have been observed blocking the binding of calmodulin to Na + channels (Choi et al, 2006;Biswas et al, 2008). In our experiments these effects may be induced by the inhibition of the binding of endogenous calmodulin.…”
Section: Discussionmentioning
confidence: 99%